Curriculum Regulation Document Analysis on Strengthening Character Values through Physical Education - Ewendi W. Mangolo; Heppy Hein Wainggai; Lestari Wulandari S; Yusinta Fransina Kabagaimu (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2025)
The implementation of the Merdeka Curriculum represents a significant reform in Indonesia’s national education system, aiming to provide greater flexibility and student-centered learning. In the context of Physical Education (PE) at the junior high school level, this curriculum seeks to enhance not only students’ physical abilities but also their character, creativity, and collaboration. This research evaluates the effectiveness of the Merdeka Curriculum in improving the quality of PE learning at State Junior High School  (SJHS) 4 Jayapura. The object of this study is the Physical Education learning process as applied under the Merdeka Curriculum at State Junior High School 4 Jayapura. The main objective is to analyze how well the curriculum promotes engaging, inclusive, and competency-based learning in PE classes. This study used a qualitative descriptive method. Data were gathered through classroom observations, interviews with PE teachers, and questionnaires distributed to students at the school. Findings indicate that the Merdeka Curriculum has a positive influence on the quality of PE learning, particularly in increasing student motivation, active participation, and the integration of character-building elements. Nonetheless, several challenges were identified, such as limited facilities, inconsistent implementation, and the need for continuous teacher training. In conclusion, the Merdeka Curriculum at State Junior High School 4 Jayapura demonstrates promising potential in enhancing PE learning. However, its success is highly dependent on adequate resources and ongoing professional development for educators.